Personalidade dos usuários e lealdade ao mercado da Comunidade Steam - Francis Marcean Resende Barros (2024)
Background and purpose: from arcade to online, the gaming market has evolved and changed its way of generating revenue. Currently, many free-to-play online games offer customization items, known as skins, or, in academic literature, as virtual goods. Based on the identification of gaps in the state of the art, this thesis proposed interactions between personality traits and behavioral variables, resulting in an original model, with valuable insights. Objective: to evaluate the antecedent constructs of continued use intention and word-of-mouth recommendation of community markets for buying and selling virtual goods from online games. Methods: this study was quantitative. The population was the community of Brazilian users of the Steam community market. Data collection was carried out through a survey, and analyzed using exploratory factor analysis, confirmatory factor analysis and structural equation modeling. Originality/Value: the relationships between personality traits and intention of continued use were explored through a hierarchical structure, breaking with the pattern presented by studies on virtual goods from online games, which showed greater concern with extrinsic motivations. Results: the results showed the multiple relationships between elemental, compound, situational and surface traits. At the surface level, the construct Intention for continued use was directly explained by the variables Attitude and Network size, while the construct Word of mouth recommendation was explained by the variables Aesthetic value, Attitude and Network size. Theoretical/methodological contributions: the study advanced the state of the art of virtual goods, proposing relationships not covered in other studies. Methodologically, it demonstrated the value of freeware software for performing data analysis, in addition to adopting practices that promote critical reflection on analysis recipes offered by commercial software.